The narrative axis and narrative space of Jeriji Kasih: a text analysis based on genuine literature - Othman, Shamsudin; Hassan @ Zulkifli, Muhammad Zarif (Dewan Bahasa dan Pustaka, 2013)
The change of literary texts for the subject of Malay Literature in schools brings with it the hope that the text chosen is one of “quality” in order to successfully reach the aims of the National Education Policy. This article is an analysis of the novel Jeriji Kasih (The Confines of Love) which supposedly is written with “an interesting story-telling technique” and is said to be able to impart “knowledge” as well as to shape students into people conscious of goodness, truth and a refined character. The analysis is based on the locallydeveloped framework of Genuine Literature (Persuratan Baru) which aims to examine the extent to which both these claims are true. The main idea in Genuine Literature is the emphasis on “knowledge” as opposed to “narrative”. This analysis shows how the text shapes a “narrative axis” and comes together in a “narrative space”. The analysis of this text also shows that the “narrative space” has been occupied with the “contents of the narrative” through the manipulation of a number of elements such as character and plot. This analysis reveals that the “knowledge” claimed to be contained in this text diverges from the idea of “knowledge” as put forth by Genuine Literature.